2020
DOI: 10.1016/j.soilbio.2020.107754
|View full text |Cite
|
Sign up to set email alerts
|

A core microbiota of the plant-earthworm interaction conserved across soils

Abstract: The core microbiota defines the fraction of microorganisms common to all individuals from the same host species regardless of the abiotic context, be they located inside (e.g. animal guts) or outside (e.g. plant rhizospheres). While the core microbiota of many host species have been documented, no studies attempted to decipher how these core microbiota could be altered when their respective host species are interacting. We thus tested the hypothesis that interactions between different host species possessing e… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 42 publications
(18 citation statements)
references
References 56 publications
1
17
0
Order By: Relevance
“…Moreover, StARS method also allowed reducing possible biais in OTUs relative abundances between the two experiments, through the use of partial correlations. Hereafter we elaborated a network approach based on edge arithmetic ( Jacquiod et al, 2020 ) to identify OTU correlations that were specific of intercropping ( Supplementary Figure 2 ). Briefly, in the matrix of the pea and the wheat intercropping, we systematically removed all correlation interferences that were attributed to (i) the bare soil, (ii) the pea monocropping, and (iii) the wheat monocropping ( Supplementary Figure 2 ).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, StARS method also allowed reducing possible biais in OTUs relative abundances between the two experiments, through the use of partial correlations. Hereafter we elaborated a network approach based on edge arithmetic ( Jacquiod et al, 2020 ) to identify OTU correlations that were specific of intercropping ( Supplementary Figure 2 ). Briefly, in the matrix of the pea and the wheat intercropping, we systematically removed all correlation interferences that were attributed to (i) the bare soil, (ii) the pea monocropping, and (iii) the wheat monocropping ( Supplementary Figure 2 ).…”
Section: Methodsmentioning
confidence: 99%
“…An increasing attention is given to interaction networks between rhizosphere organisms ( van der Heijden and Hartmann, 2016 ) and the impact of IC on these networks has recently been stressed ( Liu et al, 2021 ; Tang et al, 2021 ). Thus, co-occurrence networks have been proposed as an additional parameter to characterize microbial communities ( Barberán et al, 2012 ; Berry and Widder, 2014 ; Morriën et al, 2017 ; de Vries et al, 2018 ; Li and Wu, 2018 ; Jacquiod et al, 2020 ). Concerning IC co-occurrence network, Tang et al (2021) showed, through a shotgun metagenome analysis, that sugarcane and peanut IC increased the abundance of bacterial genes involved in organic matter turnover comparing to SC, without correlating these differences to changes in microbiota diversity.…”
Section: Introductionmentioning
confidence: 99%
“…We investigated the structure of the modern and ancient wheat varieties rhizosphere microbiota using a network approach based on edge arithmetic (Jacquiod et al 2020) to focus on OTU correlations that are specific of each type of breeding. We first calculated two separated partial correlation matrices amongst dominant rhizosphere OTUs (total summed counts = 100 minimum, occurrence = 25/51 samples), one for the modern and one for the ancient varieties using Poisson Log Normal models (PLN, package ‘ PLNmodels ‘, Chiquet et al 2019).…”
Section: Methodsmentioning
confidence: 99%
“…In the case of autogenic engineers, the functional domain is delineated by the engineering organism itself while in the case of allogenic engineers its boundary corresponds to the part of the environment which is modified by the activity of the engineering organism. Another consequence of the distinction between allo-and autogenic engineers is that the former allows positive interactions with another organism having engineering properties, as in the intermingling functional domains of roots and earthworms, with a function synergy between them (Jacquiod et al, 2020), a typical case of "cooperative ecosystem engineering" (Passarelli et al, 2014). In the case of autogenic engineers, a synergy may exist between their functional domains provided they are self-compatible.…”
Section: Communities Are Shaped By Ecosystem Engineersmentioning
confidence: 99%
“…Processing chains can explain successions observed in the course of decomposition (Paradise, 2000;Ponge, 2005b). Several engineers may also interact and display synergetic effects, like in core microbiota of plant-earthworm interactions (Jacquiod et al, 2020).…”
Section: Species Interactions Are Fashioned By Ecosystem Engineersmentioning
confidence: 99%